Maine in the 104th Congress: Life without Mitchell - Palmer, Kenneth; Taylor, G. (Maine Policy Review, 1995)
For many Mainers, the significance of the last election had little to do with the Republican "sweep" throughout the nation, but had much to do with the retirement of Senator George Mitchell. This article summarizes Senator Mitchell’s most critical policy contributions and the results of his influence at the state and national levels. His absence from Congress presents the currentMainedelegation with a new set of challenges. These issues are explored, in part, from the broader perspective ofMaine’s history in Congress.